The influence of obesity predictors toward percentage body fat among adolescences in Kelang, Selangor / Zarizi Ab Rahman … [et al.] - Ab Rahman, Zarizi; Hashim, Ahmad; Ab Latif, Rozita; Mohd Noor, Mohad Anizu (Faculty of Sports Science and Recreation, University Press of Universiti Teknologi MARA, 2020)
Obesity among adolescents had becoming a global epidemic in recent years. It was a challenging health problem with the increasing prevalence of obesity for the group. Prevalence of obesity was not considered a health threat to humans but also increased the economic burden on families and countries. Obesity was primarily caused by an increase in body fat percentage due to the energy imbalance between calorie intake and consumption. The effects of this energy imbalance were causing the accumulation and excess of body fat. There were various factors that predict obesity such as self-efficacy, motor skills, school environment, media, community, family, nutrition, sedentary behaviour, health knowledge, physical fitness and socioeconomic status. Complex risk factors make some obesity interventions difficult to achieve successfully and most of these programs failed. The theory or model of health promotion and disease prevention programs considered the importance of the various factors, health issues that need to be addressed, and the populations involved before any preventive measures were planned and implemented. Therefore, this study aimed to determine the effect of obesity predictor factors on boys and girls aged 13 to 14 in Kelang, Selangor. This quantitative study involved 150 sample students from Seri Andalas National Secondary School, Klang, Selangor (L = 32, P = 48) and the Rantau Panjang National Secondary School, Klang, Selangor (L = 30, P = 40) through simple random sampling techniques. Predictors of obesity factors and body mass index were used to collect data. Descriptive and inferential statistics were used for data analysis. Multivariate regression analysis found that all predictor factors are significant for body fat percentage, with eating behaviour was the primary predictor. As a result, aspects of healthy eating need to specifically focus on adolescents and children in an effort to address the prevalence of obesity.